Obstacles and supportive behaviours to end-of-life care in adult intensive care units: perceptions of intensive care nurses - Dorsaa, Patricia (My University, 2019)
Background: Despite the efforts of Intensive Care clinicians to save lives, the Intensive Care Unit is a common place of death. Globally, one out five (20%) Intensive Care admissions die before, or shortly after discharge. Evidence indicates that critically ill patients are at risk of having their end-of-life care needs unmet. Intensive Care nurses are mandated to provide optimal end-of-life care to dying patients and their families, however, these nurses are reported to face challenges providing optimal care and sometimes suffer moral distress. These, and the limited studies on obstacles and supportive behaviours to providing end-of-life in adults ICUs in South Africa, necessitates studies on the phenomenon to help improve care for dying patients and their families. Purpose: The purpose of this study was to identify and describe the obstacles and supportive behaviours to providing end-of-life care in adult ICUs as perceived by Intensive Care nurses. Method: A non-experimental quantitative descriptive survey and cross-sectional design was used for this study. The entire population of Intensive Care nurses in adult ICUs in the selected study site were invited to participate in the study. The National Survey of Critical-Care Nurses Regarding End-of-Life Care Questionnaire, developed by Beckstrand and Kirchhoff (2005), was adopted for data collection. Data was collected in one month and analysed with STATISTICA statistical software version 13.2. Descriptive statistical tests, including measures of frequency, central tendency and dispersions, were used to analyse the data. Hsieh and Shannon’s (2005) descriptive summative method of content analysis was used to analyse open-ended questions. Setting: The study was conducted in five adult ICUs namely cardiothoracic, coronary care, multidisciplinary, neurosurgery and trauma ICUs of an academic hospital in Johannesburg. Results: 91 Intensive Care nurses from the five adult ICUs completed the survey, representing 86.7% response rate. The top three perceived obstacles were, frequent calls from family for update on patient, nurses having to deal with distraught family and dealing with angry family members. The three largest and most frequently occurring supportive behaviours were allowing families adequate time to be alone with the patient after death, providing peaceful and dignified bedside scene for the family after the patient’s death and having the physician meet the bereaved family in person after the patient’s death to offer support. Conclusion: The major obstacles and supportive behaviours to optimal end-of-life care in adult ICUs are related to patient family issues. This may be attributed to the uniqueness of each families’ needs.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2019